Penetration of non-uniform electromagnetic field into conducting body - Vasetsky, Yu. M. (Національний технічний університет "Харківський політехнічний інститут", 2021)
The study is based on the exact analytical solution for the general conjugation problem of three-dimensional quasi-stationary field at a flat interface between dielectric and conducting media. It is determined that non-uniform electromagnetic field always decreases in depth faster than uniform field. The theoretical conclusion is confirmed by comparing the results of analyticaland numerical calculations. The concept of strong skin effect is extended to the case when penetration depth is small not only compare to the characteristic body size, but also when the ratio of the penetration depth to the distance from the surface of body to the sources of the external field is small parameter. For strong skin effect in its extended interpretation, the influence of external field non-uniformity to electromagnetic field formation both at the interface between dielectric and conducting media and to the law of decrease field in conducting half-space is analyzed. It is shown, at the interface the expressions for the electricand magnetic intensities in the form of asymptotic series in addition to local fieldvalues of external sources contain their derivatives with respect to the coordinate perpendicular to the interface. The found expressions made itpossible to generalize the approximate Leontovich impedance boundary condition for diffusion of non-uniform field into conducting half-space. The difference between the penetration law for the non-uniform field and the uniform one takes place in the terms of the asymptotic series proportionalto the small parameter to the second power and to the second derivative with respect to the vertical coordinate from the external magnetic field intensity at the interface.

Дослідження засноване на точному аналітичному розв’язку загальної задачі спряження тривимірного квазістаціонарного поля на межі розділу діелектричного і електропровідного середовищ. Встановлено, що неоднорідне електромагнітне поле завжди зменшується в глибині швидше, ніж однорідне. Теоретичний висновок підтверджується зіставленням результатів аналітичних і чисельних розрахунків. Поняття сильного скін-ефекту поширюється на випадок, коли глибина проникнення мала порівняно не тільки з характерними розмірами тіла, але також коли відношення глибини проникнення до відстані від поверхні тіла до джерел зовнішнього поля є малим параметром. Для сильного скін-ефекту в його розширеної інтерпретації проаналізовано вплив неоднорідності зовнішнього поля на формування електромагнітного поля на межі і на закон зменшення поля в провідному півпросторі. Показано, що на межі вирази у вигляді асимптотичних рядів крім локальних значень поля зовнішніх джерел містять їх похідні по координаті, перпендикулярної граничної поверхні. Отримані вирази дозволили узагальнити наближену імпедансну граничну умову Леонтовича для дифузії неоднорідного поля в провідний півпростір. Відмінність законів проникнення для неоднорідного і однорідного полів має місце в членах асимптотичного ряду, пропорційних малому параметру в другому ступені і другій похідній по вертикальній координаті від напруженості зовнішнього магнітного поля у граничній поверхні.
Keywords: three-dimensional electromagnetic field; electromagnetic field formation; exact analytical solution; skin effect; тривимірне електромагнітне поле; формування електромагнітного поля; точний розв’язок задачі; скін-ефект